Experimental and clinical progress of in utero hematopoietic cell transplantation therapy for congenital disorders - Shi, Chunyu; Pan, Lu; Hu, Zheng (Frontiers in Pharmacology, 2022)
In utero hematopoietic cell transplantation (IUHCT) is considered a potentially efficient therapeutic approach with relatively few side effects, compared to adult hematopoietic cell transplantation, for various hematological genetic disorders. The principle of IUHCT has been extensively studied in rodent models and in some large animals with close evolutionary similarities to human beings. However, IUHCT has only been used to rebuild human T cell immunity in certain patients with inherent immunodeficiencies. This review will first summarize the animal models utilized for IUHCT investigations and describe the associated outcomes. Recent advances and potential barriers for successful IUHCT are discussed, followed by possible strategies to overcome these barriers experimentally. Lastly, we will outline the progress made towards utilizing IUHCT to treat inherent disorders for patients, list out associated limitations and propose feasible means to promote the efficacy of IUHCT clinically.